Circulating miR‐203 derived from metastatic tissues promotes myopenia in colorectal cancer patients. Issue 3 (25th March 2019) - Okugawa, Yoshinaga; Toiyama, Yuji; Hur, Keun; Yamamoto, Akira; Yin, Chengzeng; Ide, Shozo; Kitajima, Takahito; Fujikawa, Hiroyuki; Yasuda, Hiromi; Koike, Yuhki; Okita, Yoshiki; Hiro, Junichiro; et al.
Abstract: Background: Sarcopenia frequently occurs in metastatic cancer patients. Emerging evidence has revealed that various secretory products from metastatic tumours can influence host organs and promote sarcopenia in patients with malignancies. Furthermore, the biological functions of microRNAs in cell‐to‐cell communication by incorporating into neighbouring or distal cells, which have been gradually elucidated in various diseases, including sarcopenia, have been elucidated. Methods: We evaluated psoas muscle mass index (PMI) and intramuscular adipose tissue content (IMAC) using pre‐operative computed tomography imaging in 183 colorectal cancer (CRC) patients. miR‐203 expression levels in CRC tissues and pre‐operative serum were evaluated using quantitative polymerase chain reaction. Functional analysis of miR‐203 overexpression was investigated in human skeletal muscle cells (SkMCs), and cells were analysed for proliferation and apoptosis. Expressions of several putative miR‐203 target genes (CASP3, CASP10, BIRC5, BMI1, BIRC2, and BIRC3) in SKMCs were validated. Results: A total of 183 patients (108 men and 75 women) were included. The median age of enrolled patients at diagnosis was 68.0 years (range 35–89 years). High IMAC status significantly correlated with female gender ( P  = 0.004) and older age ( P  = 0.0003); however, no other clinicopathological factors correlated with IMAC status in CRC patients. In contrast, decreased PMI significantly correlated with female gender ( P  = 0.006) and all well‐established disease development factors, including advanced T stage ( P  = 0.035), presence of venous invasion ( P  = 0.034), lymphovascular invasion ( P  = 0.012), lymph node ( P  = 0.001), distant metastasis ( P  = 0.002), and advanced Union for International Cancer Control tumour–node–metastasis stage classification ( P  = 0.0004). Although both high IMAC status and low PMI status significantly correlated with poor overall survival (IMAC: P  = 0.0002; PMI: P  < 0.0001; log‐rank test) and disease‐free survival (IMAC: P  = 0.0003; PMI: P  = 0.0002; log‐rank test), multivariate Cox's regression analysis revealed that low PMI was an independent prognostic factor for both overall survival (hazard ratio: 4.69, 95% confidence interval (CI): 2.19–10, P  = 0.0001) and disease‐free survival (hazard ratio: 2.33, 95% CI: 1.14–4.77, P  = 0.021) in CRC patients. Serum miR‐203 expression negatively correlated with pre‐operative PMI level ( P  = 0.0001, ρ  = −0.25), and multivariate logistic regression analysis revealed that elevated serum miR‐203 was an independent risk factor for myopenia (low PMI) in CRC patients (odds ratio: 5.16, 95% CI: 1.8–14.8, P  = 0.002). Overexpression of miR‐203 inhibited cell proliferation and induced apoptosis via down‐regulation of BIRC5 (survivin) expression in human SkMC line. Conclusions: Assessment of serum miR‐203 expression could be used for risk assessment of myopenia, and miR‐203 might be a novel therapeutic target for inhibition of myopenia in CRC.